1996
DOI: 10.1007/s004210050107
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of kinetics of electromyogram spectrum parameters during dynamic exercise

Abstract: During incremental exercise on a cycle ergometer a study was made of the reproducibility of changes in electromyographic activity (EMG) of human quadriceps muscles. Seven subjects performed three periods of incremental exercise either every 2 weeks (G1: four subjects) or 6 weeks (G2: three subjects). Each test was normalized with respect to the maximal aerobic power (MAP) of the subject. It consisted of a quasilinear increase in mechanical power (from 20% to 100% MAP) during 8 min. For rectus femoris muscle ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…On the other hand, standardization with respect to EMG changes recorded at 0 W could lead to overestimation of end-of-exercise activity when a given muscle was not activated at all at the onset of exercise. In order to avoid such misinterpretations of EMG data, RMS values were normalized with respect to the RMS max value recorded during the incremental exercise as previously reported [8,13]. Surface electromyography is commonly used for assessment of muscular function during different types of dynamic exercise such as cycling, running or isokinetic repeated contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, standardization with respect to EMG changes recorded at 0 W could lead to overestimation of end-of-exercise activity when a given muscle was not activated at all at the onset of exercise. In order to avoid such misinterpretations of EMG data, RMS values were normalized with respect to the RMS max value recorded during the incremental exercise as previously reported [8,13]. Surface electromyography is commonly used for assessment of muscular function during different types of dynamic exercise such as cycling, running or isokinetic repeated contractions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to the best of our knowledge, only few studies showed the reproducibility of the EMG parameters during isokinetic repeated contractions [16,17] or throughout an incremental cycling exercise performed until exhaustion [8]. However, in the former, only few muscles (vastus medialis, vastus lateralis and rectus femoris) were recorded.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, standardization with respect to EMG changes recorded at 0 W could lead to overestimation of end-of-exercise activity when a given muscle is not activated at all at the onset of exercise. In order to avoid such misinterpretations of EMG data, we normalized RMS values with respect to the RMS max value recorded during the incremental exercise as previously reported (Gamet et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Since muscle activity has been shown to be repeatable during incremental cycling (Laplaud et al, 2006;Gamet et al, 1996), it could be assumed that the changes found in muscle activity during each cycling load was highlighted more by the type of method of normalisation used and not entirely due to the variation in muscle activity caused by fatigue or from the intrinsic and extrinsic influences on the EMG signal. In this study the aim was to measure the ability of each method to detect changes in muscle activity over five stages of the PPO test and also during the final stage of the PPO trial.…”
Section: Sensitivity Of the Methods Of Normalisationmentioning
confidence: 99%